2016
DOI: 10.1016/j.jjcc.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates and prognostic values of pseudoinfarction in cardiac light-chain amyloidosis

Abstract: The presence of pseudoinfarction on the ECG has a negative prognostic effect on AL patients with cardiac involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 24 publications
(22 reference statements)
0
13
1
3
Order By: Relevance
“…In patients with cardiac amyloidosis, low voltage in limb leads, poor R progression, and pseudoinfarction were the most common findings 14‐16 . Low voltage QRS, pseudoinfarction and fragmented QRS was associated with adverse outcomes in cardiac amyloidosis defined by either endomyocardial biopsy or echocardiographic evidence 14,17,18 . However, in our study, the prevalence of low voltage in limb leads was far below that in other studies and did not correlate with poor prognosis.…”
Section: Discussioncontrasting
confidence: 72%
“…In patients with cardiac amyloidosis, low voltage in limb leads, poor R progression, and pseudoinfarction were the most common findings 14‐16 . Low voltage QRS, pseudoinfarction and fragmented QRS was associated with adverse outcomes in cardiac amyloidosis defined by either endomyocardial biopsy or echocardiographic evidence 14,17,18 . However, in our study, the prevalence of low voltage in limb leads was far below that in other studies and did not correlate with poor prognosis.…”
Section: Discussioncontrasting
confidence: 72%
“…In our study, we included only patients with cardiac AL amyloidosis confirmed by endocardial biopsy, a confirmatory diagnostic method, and there were some patients with equivocal echocardiographic findings even with positive endocardial biopsy. Previous studies have suggested that the presence of pseudoinfarction and fragmented QRS is associated with prognosis in cardiac AL amyloidosis defined by either endomyocardial biopsy or echocardiographic evidence in systemic amyloidosis 9,10 . However, neither pseudoinfarction nor fragmented QRS showed prognostic value in our study.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that among patients with AL cardiac amyloidosis, low QRS voltage can be detected in 23-64% of patients 5-7 , while the pseudo-MI pattern can be detected in 15-69% 5, 8 . Furthermore, both low QRS voltages 5, 8 and pseudo-MI patterns 15,16 have been reported to be predictive of a poor prognosis in cardiac amyloidosis.…”
Section: Discussionmentioning
confidence: 99%